The role of critical life events in the talent development pathways of athletes and musicians: A systematic review - John, J. M.; Gropper, H.; Thiel, A. (Psychology of Sport and Exercise, 2019)
Objectives: The experience of critical life events may be crucial for talent development. Critical life events can shape individual biographies and are landmarks in defining narrative identities. However, there is a lack of systematic research on life events in the context of talent development. With this systematic review, we synthesize the literature on the role of critical life events in the biopsychosocial developmental pathways of athletes and musicians. Method: The systematic review was informed by the PRISMA guidelines. The identified literature was appraised with the Mixed Methods Appraisal Tool. Additionally, we conducted a thematic network analysis. Results: Thirty-six studies met the inclusion criteria. Three thematic networks emerged from the findings: Types of life events; coping strategies; and impact of life events on the developmental pathway. The findings suggest that critical life events are not necessarily traumatic or hinder the biopsychosocial development of athletes and musicians. Performers can benefit from various life events with regard to their development - dependent on the coping strategies employed. Conclusions: Against the background of our findings, practitioners should consider to systematically use the benefits of challenges. These should be explicitly career-related, manageable, and focused on the refinement of skills.